"Operational" concepts in the phenomenon of Islamist radicalization: From the subject to the apocalypse - Jaccard, Annabelle; Tiscini, Giorgia (International journal of psychoanalysis, 2021)
Taken from interviews with men having been incarcerated on the charge of criminal association with the intent of committing or aiding and abetting to terrorist acts, the central question of this article has thus emerged: which part does Islamist radicalization play on the psychic level of the self? Therefore, we have selected several theorical concepts, to guide us in this research, that became operative concepts, such as hatred, drive, melancholy and symptom. These have a converging point that is linked with the clinic of boredom and emptiness, or named otherwise, "off language". The radicalization process seems to come as a way to fill this emptiness, and hence to avoid the risk of the collapsing of the self. However, this "solution" is only a lure, leading to destruction, while at the same time, the person is aiming to restore its identity.